Impact of 18-Month Soy Protein Supplementation on Steroid Hormones and Serum Biomarkers of Angiogenesis, Apoptosis, and the Growth Hormone/IGF-1 Axis: Results of a Randomized, Placebo-Controlled Trial in Males Following Prostatectomy. (2nd January 2022) - Bosland, Maarten C.; Huang, Jonathan; Schlicht, Michael J.; Enk, Erika; Xie, Hui; Kato, Ikuko
Abstract: Many studies have addressed the effects of dietary supplementation with soy protein on cancer risk and mortality, but there are only few randomized studies with soy in males. We used serum samples from a two-year trial of soy protein isolate supplementation in middle-aged to older males at risk of recurrence of prostate cancer after radical prostatectomy to determine soy effects on steroid hormones involved in prostate cancer (testosterone, SHBG, and estradiol) and explore the effects on biomarkers of the growth hormone/IGF-1 axis, apoptosis, and angiogenesis. Compared with a casein-based placebo, 18 mo, of consumption of 19.2 g/day of whole soy protein isolate containing 24 mg genistein-reduced circulating testosterone and SHBG, but not free testosterone, and did not affect serum concentrations of estradiol, VEGF, IGF-1, IGFBP-3, IGF-1/IGFBP-3 ratio, soluble Fas, Fas-ligand, and sFas/Fas-ligand ratio. Thus, soy protein supplementation for 18 mo, affected the androgen axis, but the effects on other cancer biomarkers remain to be more definitively determined. The study was registered at clinicaltrials.gov (NCT00765479).